Analysis Junior High School Students' Conceptual Understanding of Flat-Sided Space Structures Based on Bloom's Taxonomy - Ahmad ubaidillah; Luluk Faridah; Khafidhoh Nurul Aini (Program Studi Pendidikan Matematika Universitas Katolik Santo Agustinus Hippo, 2025)
This study aims to analyze junior high school students' conceptual understanding in solving problems on three-dimensional with flat surfaces based on the revised Bloom's Taxonomy. This research employed a descriptive qualitative method with 6 seventh-grade students of SMP Negeri 1 Glagah , selected through purposive sampling. The research instruments consisted of essay tests and semi-structured interview guidelines referring to the six cognitive levels of Bloom's Taxonomy (C1–C6) and validated by experts. The data were analyzed through data reduction, data display, and conclusion drawing, with methodological triangulation to ensure the validity of the findings. The results showed that 13% of students were in the high category, 73% in the medium category, and 13% in the low category. High-category students mastered all conceptual understanding indicators, while medium- and low-category students experienced difficulties at the analyzing (C4), evaluating (C5), and creating (C6) levels. These findings indicate the need for learning strategies that enhance higher-order thinking skills through contextual problem-solving, the use of visual media, and problem-based learning.